SenseCam improves memory for recent events and quality of life in a patient with memory retrieval difficulties - Browne, G.; Berry, E.; Kapur, N.; Hodges, Steve; Smyth, Gavin; Watson, P.; Woodberry, Ken (Memory, 2011)
A wearable camera that takes pictures automatically, SenseCam, was used to generate images for rehearsal, promoting consolidation and retrieval of memories for significant events in a patient with memory retrieval deficits. SenseCam images of recent events were systematically reviewed over a 2-week period. Memory for these events was assessed throughout and longer-term recall was tested up to 6 months later. A written diary control condition followed the same procedure. The SenseCam review procedure resulted in significantly more details of an event being recalled, with twice as many details recalled at 6 months follow up compared to the written diary method. Self-report measures suggested autobiographical recollection was triggered by the SenseCam condition but not by reviewing the written diary. Emotional and social wellbeing questionnaires indicated improved confidence and decreased anxiety as a result of memory rehearsal using SenseCam images. We propose that SenseCam images provide a powerful boost to autobiographical recall, with secondary benefits for quality of life.